Cavernous Hemangioma: Uncommon Cause of Obscure Gastrointestinal Bleeding Diagnosed by Video Capsule Endoscopy and Contrast Enhanced Computed Tomography - Monreal-Robles, Roberto; Aguilera, Angel Noe del Cueto-; García-Compean, Diego; González, Jose Alberto González-; Borjas-Almaguer, Omar David; O, Joel (Archives of Clinical and Medical Case Reports, 2020)
We present the case of a 63-year-old woman with obscure gastrointestinal bleeding (OGIB) due to jejunal cavernous hemangioma diagnosed by video capsule endoscopy (VCE), contrast enhanced computed tomography (CECT) and CT angiography, who was successfully treated with surgical resection. Small bowel cavernous hemangioma is a rare cause of OGIB, most commonly presenting as an iron-deficiency anemia. Two decades ago, the preoperative diagnosis was quite difficult. Currently, the use of VCE and device assisted enteroscopy (DAE) allow detection of the lesion. Biopsy is not recommended due to the risks of uncontrolled bleeding. The use of CECT and CT angiography may be useful for demonstrate the vascular nature of the lesion, and define localization, number and extension of the lesion preoperatively in order to improve surgical results as was observed in our patient. Surgery is the most frequent treatment, notwithstanding, endoscopic resection of lesions has been recently reported. However, the experience is small and there are serious limitations of this technique.